FESTAS, ALIMENTOS E COMUM: TERRITÓRIO E CULTURA NA FOZ DO RIO DOCE - Goulart, Vitor Mendes (2020)
The following research is part of an effort to better understand a specific territory: the Village of Regência Augusta, located on the right mouth of the Rio Doce in Espírito Santo. The study is based on the identification of three key elements, namely, f